Impact of government law on edible oil supply chain in Bangladesh Perspective - Reaz Ameen Choudhury; Meghla Clara Costa (International Journal of Supply Chain Management, 2012)
Abstract-This descriptive study is not intended as a detailed analysis; its aim is to present an overall view of the impact of a government law regarding edible oil marketing and distribution in Bangladesh. Social, economic, environmental and sustainability issues are not covered in this report. All the data of this report is collected from secondary source. This study is going to deliver contribution to the new investors who are going to invest in this industry, existing industries for legal compliance and process improvement. The academics can use this report for analyzing market scenario and Bangladesh government authorities can use it partially for monitoring market and decision making purpose.